(NbIBLIOTEKA (B"(NoGONEK(B". (NoTE^ESTWENNAQ KLASSIKAs - (NgOGOLX(B, (NnIKOLAJ wASILXEWI^s ((NmOSKWA(B:s (NpRAWDA(B,s, 1984)
(NsOBRANIE SO^INENIJ W WOSXMI TOMAHs
rus
Keywords: (NpOWESTI I RASSKAZYs; (NdRAMAs; (NpISXMAs; (NmISTIKAs